ChemInform Abstract: Probing the Zintl—Klemm Concept: A Combined Experimental and Theoretical Charge Density Study of the Zintl Phase CaSi. Issue 24 (2nd June 2014) - Kurylyshyn, Iryna M.; Faessler, Thomas F.; Fischer, Andreas; Hauf, Christoph; Eickerling, Georg; Presnitz, Manuel; Scherer, Wolfgang
Abstract The nature of the chemical bonds in the Zintl phase CaSi is investigated by a combined experimental and theoretical charge density analysis to test the validity of the Zintl‐Klemm concept.